The late Hellenistic tetradrachms of Parion and Lampsakos - Ellis Evans, A (American Numismatic Society, 2021)
This article presents die studies of the tetradrachms minted by Parion and Lampsakos in the Hellenistic period. The Parion Group 1 tetradrachms date to the late 160s or 150s, whereas the Parion Group 2 and Lampsakos tetradrachms date not to the second quarter of the 2 nd century as previously thought, but rather to the early 1st century. The overlooked evidence of IGCH 1322 (western Asia Minor, 1964/5) provides proof for this later date in the case of Lampsakos. New evidence about the composition of IGCH 1322 is presented which allows some progress to be made in identifying the contents of this hoard. The down-dating of these two coinages has two broader consequences. Firstly, Lampsakos’ decision to depict Priapos on its coins for the first time with this series should be connected to an epiphany of Priapos which occurred during the war with Aristonikos and significantly altered the god’s status at Lampsakos for the rest of antiquity. Secondly, the downdating of the Parian and Lampsakene series to a period of direct Roman rule raises the question of the degree to which Rome was involved in the production of these coinages.